Índice Homeostasis Model Assesment para el diagnóstico de resistencia insulínica. - Moreta Ramírez, María Fernanda (2023)
Insulin resistance is defined as the metabolic state in which the tissue effects of insulin are decreased, particularly at the level of muscle and adipose tissue, with consequent compensatory hyperinsulinemia, which is related to cardiovascular risk, type 2 diabetes mellitus, non-alcoholic fatty liver, polycystic ovarian syndrome, and some cancers. The present work was carried out through a bibliographic review to evaluate the usefulness of the Homeostasis Model Assessment Index to diagnose insulin resistance through a descriptive, documentary, and non-experimental, retrospective study. Seventy-two scientific articles were analyzed and selected using the inclusion and exclusion criteria. Information from databases such as Scielo, Redalyc, Elsevier Proquest, Medigraphic, Pub Med, and Google Scholar was analyzed from no more than ten years in Spanish and English. The research showed that the HOMA-IR index is the gold standard (90%) for assessing insulin resistance (Pre-Diabetes). In addition, it was found that overweight, obesity, and circumference are the major determining factors for insulin resistance to occur in the Homeostasis Model Assenment index. This index is calculated by multiplying the result of glycemia and insulinemia divided by the constant 405. The main analysis techniques currently used to quantify glucose correspond to spectrophotometry, while chemiluminescence is used to determine insulin due to its high sensitivity and specificity.